Propofol-ketamine versus dexmedetomidine-ketamine for sedation during upper gastrointestinal endoscopy in pediatric patients: a randomized clinical trial - Amer,Akram M. (2020)
Abstract Background and objectives Day-case pediatric sedation is challenging. Dexmedetomidine is a sedative analgesic that does not induce respiratory depression. We compared dexmedetomidine to propofol when it was added to ketamine for sedation during pediatric endoscopy, regarding recovery time and hemodynamic changes. Methods We enrolled 120 patients (2−7 years in age) and randomly assigned them into two groups. Each patient received intravenous (IV) ketamine at a dose of 1 mg.kg-1 in addition to either propofol (1 mg.kg-1) or dexmedetomidine (0.5 µg.kg-1). The recovery time was compared. Hemodynamics, oxygen saturation, need for additional doses, postoperative complications and endoscopist satisfaction were monitored. Results There was no significant difference in hemodynamics between the groups. The Propofol-Ketamine (P-K) group showed significantly shorter recovery times than the Dexmedetomidine-Ketamine (D-K) group (21.25 and 29.75 minutes, respectively, p < 0.001). The P-K group showed more oxygen desaturation. Eleven and 6 patients experienced SpO2 < 92% in groups P-K and D-K, respectively. A significant difference was noted regarding the need for additional doses; 10% of patients in the D-K group needed one extra dose, and 5% needed two extra doses, compared to 25% and 20% in the P-K group, respectively (p = 0.001). The P-K group showed less post-procedure nausea and vomiting. No statistically significant difference between both groups regarding endoscopist satisfaction. Conclusions The P-K combination was associated with a shorter recovery time in pediatric upper gastrointestinal endoscopy, while the D-K combination showed less need for additional doses. Registration number Clinical trials.gov (NCT02863861).